PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT SISWA MELANJUTKAN KE PENDIDIKAN TINGGI - Kurniawan, Dani; Syahrudin, Husni; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis entitled, "The influence of the socioeconomic status of the parents towards the interest of students continuing high school education on the students of grade XII SMA N 1 Sungai Raya Kepulauan", with the research problem, "Does the economic status of parents affect the students' interest in continuing high school education on students class XII SMA N 1 Sungai Raya Kepulauan? ". Socioeconomic status of parents is very influential with children's education, children with high socioeconomic status families will get more opportunities in their education.  The population was 103 students and the sample was 51 students. The approach used by researcher is quantitative research approach, collecting data with questionnaire. Data processed with SPSS For Windows Version 18.0. analysis of 27 items of instruments declared valid, and 3 items of instruments declared invalid, test reliability is stated all instruments> 0.6 then the instrument is feasible. Normality of data using kolmogrov-smirnov test of normally distributed data asymp value significantly of 0.862 and 0, 602 is above the probability value> 0.05. The results showed that the socioeconomic status of the parents had an influence on the students' interest in continuing high education in the students of grade XII SMA N 1 Sungai Raya Kepulauan in the show with the formulation Y = 31,988 + 0,186X. Based on the calculation using SPSS computer program, t arithmetic of 1.782 is not t table with 41 respondents orrang, then t table is 1.6829. From these results, compared between t arithmetic with t table. Resulted that t count> t table that is 1,782> 1,6829, because t count> t table then Ho rejected and Ha accepted.  Keywords: Influence, Socioeconomic Status, Interests, Higher Education